2021
DOI: 10.1155/2021/2867913
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Characteristics and Empirical Research Model of Infectious Mononucleosis Complicated with Mycoplasma pneumoniae or/and Cytomegalovirus Infection

Abstract: To study the clinical features of infectious mononucleosis (IM) caused by Epstein-Barr virus (EBV) mixed with Mycoplasma pneumonia (MP) or/and cytomegalovirus (CMV)infection, collected 201 hospitalized children who met the IM diagnostic criteria, the clinical manifestations, laboratory tests, complications, treatment, and outcome were compared among EBV infection alone and EBV mixed with MP or/and CMV infection. Most of the children with IM were preschoolers, more frequently occurred in boys than girls. EBV pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%